High‐fat and high‐sucrose (western) diet induces steatohepatitis that is dependent on fructokinase. Issue 5 (8th October 2013) - Ishimoto, Takuji; Lanaspa, Miguel A.; Rivard, Christopher J.; Roncal‐Jimenez, Carlos A.; Orlicky, David J.; Cicerchi, Christina; McMahan, Rachel H.; Abdelmalek, Manal F.; Rosen, Hugo R.; Jackman, Matthew R.; MacLean, Paul S.; Diggle, Christine P.; et al.
<x xml:space="preserve">Abstract</x> Fructose intake from added sugars has been implicated as a cause of nonalcoholic fatty liver disease. Here we tested the hypothesis that fructose may interact with a high‐fat diet to induce fatty liver, and to determine if this was dependent on a key enzyme in fructose metabolism, fructokinase. Wild‐type or fructokinase knockout mice were fed a low‐fat (11%), high‐fat (36%), or high‐fat (36%) and high‐sucrose (30%) diet for 15 weeks. Both wild‐type and fructokinase knockout mice developed obesity with mild hepatic steatosis and no evidence of hepatic inflammation on a high‐fat diet compared to a low‐fat diet. In contrast, wild‐type mice fed a high‐fat and high‐sucrose diet developed more severe hepatic steatosis with low‐grade inflammation and fibrosis, as noted by increased CD68, tumor necrosis factor alpha, monocyte chemoattractant protein‐1, alpha‐smooth muscle actin, and collagen I and TIMP1 expression. These changes were prevented in the fructokinase knockout mice. Conclusion: An additive effect of high‐fat and high‐sucrose diet on the development of hepatic steatosis exists. Further, the combination of sucrose with high‐fat diet may induce steatohepatitis. The protection in fructokinase knockout mice suggests a key role for fructose (from sucrose) in this development of steatohepatitis. These studies emphasize the important role of fructose in the development of fatty liver and nonalcoholic steatohepatitis. (Hepatology 2013;58:1632–1643)